The European Union as a long-term political actor: an overview - Vogt Henri; Pukarinen Aappo (TAYLOR & FRANCIS LTD, 2022)
This paper provides an overview of the time perspectives with which the European Union conducts its politics and policies - an aim that has garnered very little scholarly attention thus far. We ask in which ways and to what extent is the Union able to employ long-term policy targets and considers the possible interests of future generations. Which factors determine the time perspectives, which institutions define them and what can possibly be done in order to employ longer-term perspectives in a more systematic manner within this complex technocratic system? We approach these questions from three viewpoints: the foundational ideas of integration; the governance structures within the EU system; and the Union's policy objectives. In addition to analyses of EU documentary data, our reflections rely on a set of semi-structured interviews conducted with a group of EU-experts in the autumn of 2019. A range of governance logics and mechanisms already support long-termism in the EU, but much can still be done in order to create a real processual value supporting it.